2008
DOI: 10.1055/s-2008-1070385
|View full text |Cite
|
Sign up to set email alerts
|

Plasmakonzentration und systemische Wirkung von Betamethason nach intraartikulärer Injektion

Abstract: Plasma concentrations of betamethasone, cortisol and corticosterone were measured before and after intraarticular injection of a betamethasone-depot preparation (Celestan-Depot) by radioimmuno-assay in 31 patients. Plasma concentration of betamethasone reached its maximum of between of 10 and 17 microgram/dl 30 min after injection. It had fallen to half after 2 hours, and practically to nil from the eighth day onwards. Lowest plasma levels of cortisol and corticosterone occurred after 6--24 hours, returning to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…There are pros and cons for simultaneous IAIs; the pros include ( a ) saving money and time; ( b ) continuous knee pain at 1 side may overshadow the improvement in the other side; ( c ) bilateral improvement may have remarkable impact on patient mobility, stability, and function; ( d ) the SAI was subclinical and transient; ( e ) a second IAI performed later may even cause a prolonged SAI. 18 …”
Section: Discussionmentioning
confidence: 99%
“…There are pros and cons for simultaneous IAIs; the pros include ( a ) saving money and time; ( b ) continuous knee pain at 1 side may overshadow the improvement in the other side; ( c ) bilateral improvement may have remarkable impact on patient mobility, stability, and function; ( d ) the SAI was subclinical and transient; ( e ) a second IAI performed later may even cause a prolonged SAI. 18 …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some studies have shown a decrease in plasma concentrations of cortisol (CORT) after IA administration of some GCs, which indicates inhibition of the HPA axis, and therefore, a systemic effect . Apart from CORT plasma concentrations, some of the side effects observed after IA administration of GCs also suggest systemic effect .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, some studies have shown a decrease in plasma concentrations of cortisol (CORT) after IA administration of some GCs, which indicates inhibition of the HPA axis, and therefore, a systemic effect. [28][29][30] Apart from CORT plasma concentrations, some of the side effects observed after IA administration of GCs also suggest systemic effect. 31,32 However, some authors claim that these systemic effects are due to a wrong IA administration because of the difficulties to administer the GC inside the joint.…”
Section: Introductionmentioning
confidence: 99%
“…After intra‐articular administration of a suspension, the concentration of CS in the synovial fluid peaks rapidly and reaches a level depending on the process of release of the drug from the pharmaceutical formulation, rate of bioactivation of the prodrug, and absorption from joint to blood. For example, TH suspension releases the steroid slower than TA due to its lower solubility, while TA and TH are less soluble than BP .…”
Section: Discussionmentioning
confidence: 99%